Plan estratégico de marketing para incrementar la cuota de mercado de 593 training center - Carrasco Cabrera, Roberto Isaías (2020)
In the last 10 years the city of Guayaquil and the country in general have witnessed constant growth in the field of health and sports, this transition has given way for new activities that promote these areas to be included in our society (Villacres & Álvarez, 2019). However, the current health and economic crisis caused by the Covid-19 pandemic, added to the international drop in the price of oil, and the low tax collection, has caused gyms to reinvent themselves in order to continue subsisting in a market extremely competitive……………